Survey of bacterial black rot of cabbage in Haveri, Belagavi and Dharwad district of northern Karnataka - M.R. RAVIKUMAR, K.B. YADAHALLI*and (Indian Phytopathology, 2016)
Bacterial black rot of cabbage caused by Xanthomonascampestrisp.v. campestriswhich took the major disease problem during 2015-16. Cabbage, the boon crop to the farmer suddenly turned as a big boon after the severe out break noticed in larger cabbage pockets of Haveri district. To generate the information on the outbreak of the disease and its economic impact on the crop losses, disease survey was conducted in the affected areas of Haveri district. The bacterium enters the plant principally through the hydathodes, stomata’s, and injuries on the leaves. The bacterium spreads in the vascular system of the leaf and stem, later complete blackening of head takes place. A survey was undertaken during Kharif2015-16 in major cabbage growing areas of Belagavi, Dharwad and Haveri districts of Karnataka in order to assess the disease index. The results revealed that the index of cabbage black rot ranged from 5.50 to 35.75 per cent, in all the locations surveyed. The mean PDI of districts was maximum in Belagavi district (24.2) followed by Haveri district (15.54) the least incidence was found in Dharwad district (11.66).